1975
DOI: 10.1093/infdis/132.4.384
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Response to Canine Distemper Viral Antigens in Gnotobiotic Dogs Infected with Canine Distemper Virus

Abstract: The humoral immune response to canine distemper viral antigens in gnotobiotic dogs experimentally infected with canine distemper virus was studied by the complement fixation and serum neutralization tests. Antibody titers measured by both serologic methods varied inversely with the severity of disease produced. Recovered dogs demonstrated the highest titers of antibody, whereas fatally infected dogs had little or no antibody activity in their sera. A third group of dogs, characterized by chronic persistent inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
0
1

Year Published

1977
1977
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 12 publications
3
42
0
1
Order By: Relevance
“…Há alta correlação entre os títulos de anticorpos e o nível de proteção e, devido a isso, a determinação dos níveis de anticorpos é uma medida amplamente utilizada como indicador de imunidade ao CDV e CPV, ao (Krakowka et al, 1975).…”
unclassified
“…Há alta correlação entre os títulos de anticorpos e o nível de proteção e, devido a isso, a determinação dos níveis de anticorpos é uma medida amplamente utilizada como indicador de imunidade ao CDV e CPV, ao (Krakowka et al, 1975).…”
unclassified
“…It has been suggested in previous studies by other investigators that the demonstration of IFN in the CSF obtained from dogs more than 20 days after experimental infection with CDV is a valid marker for viral persistence and severity of pathological lesions in the CNS (Tsai et al, 1982), and that an intermediate antibody response modifies the clinical course of the infection, tending to permit chronic infection rather than causing recovery from infection (Krakowka et al, 1975). As almost all of the confirmed cases in the present study retained a low level of IFNlike activity in their CSF more than 20 days post-infection and exhibited a moderate to vigorous antibody response (Table 1), it appears that they had already become persistently infected and were at transitional stages between the acute primary infection and the chronic infection with the serious neurological symptoms approximately 2 months or more post-infection.…”
Section: Discussionmentioning
confidence: 99%
“…Sera taken from the cases at the time of autopsy were tested for neutralizing antibody to CDV (Table 1) Interferon-like activity was assayed in CSF collected at the time of autopsy when the infection had already passed the critical phase (20 days post-infection; Krakowka et al, 1975) (Table l). A low level of IFN-like activity was detected in the CSF of only those dogs from whose brains infectious CDV was recovered, with the exception of Case 5, but it was not demonstrated in the CSF of dogs negative for virus isolation or in that of healthy dogs.…”
Section: Laboratory Examinationsmentioning
confidence: 99%
“…However, it is difficult to make a definitive diagnosis from the clinical signs and a serological diagnosis alone, since CDV induces severe immune suppression and lymphocyte depletion. Moreover, only a few studies have been done on the inability to produce antibodies against canine distemper virus [7,9].…”
mentioning
confidence: 99%
“…It has been experimentally demonstrated that severe or fatal cases of CDV infection had low or undetectable levels of CDV antibody, which would suggest that they were at the early stage or even the fatal [7,9]. However, there have been no serological reports on natural CDV infection.…”
mentioning
confidence: 99%